Long Term Debt and Credit Crisis in a Liquidity Constrained Economy - Rodrigo Abreu; Tiago Berriel (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
This p aper explores the interaction between a credit crunch and the maturity of government debt, focusing on its impacts on an economy with heterogeneous house holds. We find that an increase in debt maturity helps softening the economicslump that follows a credit crisis. We show that, immediately after the credit shock,there is an output drop of nearly 1% when the asset available has on average onequarter of maturity, while a contraction of only 0.6% follows when debt durationhas three quarters. The rise of asset duration indirectly enhances the income e-ectsunleashed by general equilibrium price dynamics, which benefits bondholders andthus softens the recession. On the other hand, an increase on debt duration impairsthe improvement of wealth distribution on the long run. The main contributionthis paper paper is to show that debt maturity is a key element to understand themagnitude of a recession driven by credit and its welfare consequences.
Keywords: 330; Self Insurance; Incomplete Markets; Credit Crisis; Debt Maturity